2003
DOI: 10.1021/es020762p
|View full text |Cite
|
Sign up to set email alerts
|

Testing Alternative Decision Approaches for Identifying Cleanup Priorities at Contaminated Sites

Abstract: This exploratory study compares two approaches for involving nonexpert stakeholders in difficult policy choices. Both approaches have as their goal informing members of the public about contaminated sites and involving them in decisions regarding their cleanup. The first approach focuses on technical information and seeks to improve the available knowledge base so that participants can make choices informed by detailed scientific data. This approach is similar in intent to many of the science-based initiatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 9 publications
3
57
0
Order By: Relevance
“…Providing information in a way that helps to make complex choices may also increase trust in managers which is considered a key factor in effective public participation processes (Arvai and Gregory, 2003;Davenport et al, 2007). Our results show that effective communication and open discussion on the implications of different management options may enhance positive attitudes towards forestry among local people.…”
Section: Discussionmentioning
confidence: 83%
“…Providing information in a way that helps to make complex choices may also increase trust in managers which is considered a key factor in effective public participation processes (Arvai and Gregory, 2003;Davenport et al, 2007). Our results show that effective communication and open discussion on the implications of different management options may enhance positive attitudes towards forestry among local people.…”
Section: Discussionmentioning
confidence: 83%
“…In a study in the late 1980s in West Germany, Keeney et al experimented with two public value fora to elicit the values relevant for setting longterm national energy policy (52). Such approaches often use structured decision methods (such as multiattribute utility elicitation), and have been applied to various national-level problems such as setting priorities for the clean up of contaminated sites across the United States (53), and space policy making at the National Aeronautics and Space Administration (54). Understanding what underpins specific preferences and acceptability was considered particularly important in our study because of the complex and unfamiliar nature of the energy system problem in all of its social and technical aspects.…”
Section: Challenge 3: Opening and Maintaining Deliberative Spaces Withmentioning
confidence: 99%
“…These elements were (a) background information about the nature area and its three emerging environmental management problems, (b) more detailed information presented in text and in tabular format about the human and environmental health risks associated with them, (c) a series of pre-and post-test closed-ended self-rating questions, and (d) the final funding allocation (choice) task. As with previous research of this type (e.g., 3,10,12), subjects in both the UT and SV conditions received the same basic information about the human and environmental health effects associated with the three management problems. However, there were variations between the UT and SV conditions in terms of (1) how this basic information was framed and (2) the addition, in the SV condition only, of value-focused contentsa key characteristic of past SDM approaches (5,11).…”
Section: Designmentioning
confidence: 99%
“…A short list of SDM applications includes their use for helping to clean up contaminated sites (12), set guidelines for water use by hydroelectric utilities (13), create estuarine management plans (14), and devise strategies for the protection of endangered species (15). In each of these cases, it was suggested that the use of some type of SDM approach helped to enhance the quality of the resulting decisions.…”
Section: Introductionmentioning
confidence: 99%